Current Concepts in the Mandibular Condyle Fracture Management Part I: Overview of Condylar Fracture - Kang-Young Choi (Archives of Plastic Surgery, 2012)
The incidence of condylar fractures is high, but the management of fractures of the mandibular condyle continues to be controversial. Historically, maxillomandibular fixation, external fixation, and surgical splints with internal fixation systems were the techniques commonly used in the treatment of the fractured mandible. Condylar fractures can be extracapsular or intracapsular, undisplaced, deviated, displaced, or dislocated. Treatment depends on the age of the patient, the co-existence of other mandibular or maxillary fractures, whether the condylar fracture is unilateral or bilateral, the level and displacement of the fracture, the state of dentition and dental occlusion, and the surgeonnds on the age of the patient, the co-existence of othefrom which it is difficult to recover aesthetically and functionally;an appropriate treatment is required to reconstruct the shape and achieve the function ofthe uninjured status. To do this, accurate diagnosis, appropriate reduction and rigid fixation, and complication prevention are required. In particular, as mandibular condyle fracture may cause long-term complications such as malocclusion, particularly open bite, reduced posterior facial height, and facial asymmetry in addition to chronic pain and mobility limitation, great caution should be taken. Accordingly, the authors review a general overview of condyle fracture.